GPS positioning in the Brazilian region during intense magnetic storm of the October, 29 2003 - Matsuoka, Marcelo Tomio; Camargo, PAULO DE OLIVEIRA [UNESP]; Batista, Inez Staciarini (Universidade Federal do Rio Grande do Sul, 2008)
The error due to the ionosphere in the GPS observables depends on the Total Electron Content (TEC) in the ionospheric layer. The TEC varies regularly in time and space in relation to the sunspot number, the season, the local time, the geographic position, and others. However, the TEC can suffer abrupt modifications in its behavior due to the occurrence of intense magnetic storm. On 28 October 2003, at 1110 UT, a major solar flare took place from a sunspot directly in line with the Earth. A coronal mass ejection was observed to leave the Sun in the direction of the Earth, causing an intense magnetic storm that started at 0611 UT of the following day. In this paper, GPS data from RBMC and IGS network and Digisonde data were used, to analyze the influence of the intense magnetic storm that occurred on October 29, 2003 in the behavior of TEC and in the performance of the point positioning in the Brazilian region.
Posicionamento por GPS na Região Brasileira Durante a Intensa Tempestade Geomagnética de 29 de Outubro de 2003
Keywords: Geomagnetic Storm; Global Positioning System; TEC